Gender Representation in Indonesian ELT Textbooks: The Hidden Bias - Zahra, Rani; Inawati, Iin; Ariffin, Kamisah (EDUCATUM Journal of Social Sciences, 2024)
Empirical research has highlighted the persistence of gender bias over centuries despite the global initiatives to promote gender equality and remove gender bias in various spheres including education. The contents of educational materials like textbooks can exert a crucial role in shaping and reinforcing the learners’ views and perceptions especially about gender roles. Addressing gender bias in textbooks is necessary in fostering a more equitable educational environment equitable, hence, promoting equitable society for future generations. The present study examined gender bias in three ELT Indonesian textbooks for three levels of education (When English Rings a Bell for Grade VII, When English Rings a Bell for Grade VIII, and Think Globally and Act Locally for Grade IX). Specifically, it investigated the distribution, types and the representation of gender bias in these textbooks. It employed both quantitative and qualitative methods of analysis to provide a more comprehensive outcomes on the gender bias presented in the textbooks. The findings indicate that gender bias is present in the three textbooks despite the urge by the Directorate General of Legislation and Regulations (2016) that textbooks must be devoid of gender stereotypes, bias, and discrimination. The portrayal of gender in the textbooks reinforces stereotype social constructs where men are depicted in leading and active roles, while women are usually shown in passive or secondary positions. This can affect the learners’ conscious and subconscious views on their own attitude, career choice and social behaviour. To develop educational materials that are free of gender-based stereotypes and reflect balanced representations of both genders, concerted effort from policy makers, educators, authors and publishers are important.